2008
DOI: 10.1037/h0100858
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral health in developmental disabilities: A comprehensive program of nutrition, exercise, and weight reduction.

Abstract: We review the literature on the prevalence and conditions resulting in overweight and obesity in people with intellectual disability (ID), followed by obesity treatment research with typically developing children and adaptations for children with ID. In addition to proposing directions for future research and practice, we report a comprehensive randomized control trial (RCT) of familybased behavioral intervention targeting weight loss among adolescents with Down syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
0
14
1
Order By: Relevance
“…Though some studies have shown positive outcomes with modeling of exercise with error correction (Fleming et al, 2008), it has been the goal of recent research to improve levels of physical fitness through promotion of positive peer relationships. One study showed an increase in interaction among students with significant disabilities and their peers following peer training in how to provide coaching to students with disabilities (Klavina & Block, 2008).…”
Section: Physical Activity Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though some studies have shown positive outcomes with modeling of exercise with error correction (Fleming et al, 2008), it has been the goal of recent research to improve levels of physical fitness through promotion of positive peer relationships. One study showed an increase in interaction among students with significant disabilities and their peers following peer training in how to provide coaching to students with disabilities (Klavina & Block, 2008).…”
Section: Physical Activity Interventionsmentioning
confidence: 99%
“…Organizational and individual constraints, such as resources, age limits, ease of access, motivation, skill level, and reliance on caregivers were also identified as barriers (Taliaferro & Hammond, 2016). There is also a lack of professionals who have exercise and nutrition expertise and who are also trained in instruction of people with significant disabilities (Fleming et al, 2008).…”
Section: Barriers To Knowledge and Skill Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sustainability of patient weight loss is especially pertinent for children with disabilities, given the importance of establishing healthy habits during childhood to ease the transition to adulthood. 26 While developing individualized goals and treatment plans is a strength of Brenner FIT, it may also lead to a treatment-by-indication bias.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have called attention to a dearth of studies investigating obesity among children with disabilities (Fleming et al, 2008; Grondhuis & Aman, 2014; Phillips et al, 2014; Slevin, Truesdale-Kennedy, McConkey, Livingstone, & Fleming, 2014). Nonetheless, population-level prevalence data suggest that obesity levels within this population are higher than in youth without intellectual and developmental disabilities.…”
Section: Obesity Among Youth With Intellectual and Developmental Disamentioning
confidence: 99%